GAMBARAN HISTOPATOLOGI SEL SARAF TIKUS WISTAR (RATTUS NORVEGICUS) LIKE MODEL ALZHEIMER PADA DAERAH KORTEKS SEREBRI AKIBAT INDUKSI ALUMINIUM KLORIDA - Abdillah, Tegar; Afriani, Nita; Susanti, Restu (EMPIRIS : Jurnal Sains, Teknologi dan Kesehatan, 2025)
Objective: To determine the histopathological features of the nerve cells of Wistar rats (Rattus norvegicus) like the Alzheimer's model in the cerebral cortex due to aluminum chloride induction. Method: This study uses a quantitative descriptive method. This research was conducted at the Laboratory of Anatomical Pathology, Faculty of Medicine, Andalas University. The study was conducted from January to December 2022. The sample consisted of 14 preparations with 7 preparations in each group. Calculation of nerve cells with the Image J application and calculated the percentage of damaged nerve cells. Results: Nerve cells underwent apoptosis and necrosis in rats given aluminum chloride. The mean percentage of nerve cell damage in the control group and the aluminum chloride group was 4.82% and 15.88%. Conclusion: The histopathological picture of the brain neurons of wistar rats in the cerebral cortex induced by aluminum chloride shows the appearance of neurons undergoing apoptosis and necrosis. The percentage of nerve cell damage was higher in aluminum chloride-induced mice than in mice that were not aluminum chloride-induced..